Metabolite Profiling of Hydroxycinnamate Derivatives in Plasma and Urine after the Ingestion of Coffee by Humans: Identification of Biomarkers of Coffee Consumption - Stalmach, Angélique; Mullen, William; Barron, Denis; Uchida, Kenichi; Yokota, Takao; Cavin, Christophe; Steiling, Heike; Williamson, Gary; Crozier, Alan (Drug metabolism and disposition, 2009)
Human subjects drank coffee containing 412 μmol of chlorogenic acids, and plasma and urine were collected 0 to 24 h after ingestion and were analyzed by high-performance liquid chromatography-mass spectrometry. Within 1 h, some of the components in the coffee reached nanomole peak plasma concentrations (Cmax), whereas chlorogenic acid metabolites, including caffeic acid-3-O-sulfate and ferulic acid-4-O-sulfate and sulfates of 3- and 4-caffeoylquinic acid lactones, had higher Cmax values. The short time to reach Cmax (Tmax) indicates absorption of these compounds in the small intestine. In contrast, dihydroferulic acid, its 4-O-sulfate, and dihydrocaffeic acid-3-O-sulfate exhibited much higher Cmax values (145–385 nM) with Tmax values in excess of 4 h, indicating absorption in the large intestine and the probable involvement of catabolism by colonic bacteria. These three compounds, along with ferulic acid-4-O-sulfate and dihydroferulic acid-4-O-glucuronide, were also major components to be excreted in urine (8.4–37.1 μmol) after coffee intake. Feruloylglycine, which is not detected in plasma, was also a major urinary component (20.7 μmol excreted). Other compounds, not accumulating in plasma but excreted in smaller quantities, included the 3-O-sulfate and 3-O-glucuronide of isoferulic acid, dihydro(iso)ferulic acid-3-O-glucuronide, and dihydrocaffeic acid-3-O-glucuronide. Overall, the 119.9 μmol excretion of the chlorogenic acid metabolites corresponded to 29.1% of intake, indicating that as well as being subject to extensive metabolism, chlorogenic acids in coffee are well absorbed. Pathways for the formation of the various metabolites within the body are proposed. Urinary dihydrocaffeic acid-3-O-sulfate and feruloylglycine are potentially very sensitive biomarkers for the consumption of relatively small amounts of coffee.